Kapasitas Badan Penanggulangan Bencana Daerah (BPBD) Kota Medan Dalam Program Kelurahan Tangguh Bencana (KELTANA) Di Kelurahan Aur Kecamatan Medan Maimun - Khairunnisa Arifa; Rudi Kristian Manurung (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
The Keltana Program is a program that makes kelurahans self-sufficient in adapting to and dealing with disaster threats, as well as recovering quickly from the adverse effects of disasters. This study aims to describe the capacity of the Medan City Regional Disaster Management Agency (BPBD) in the Disaster Resilient Village Program (KELTANA) in Aur Village, Medan Maimun District. The research method used is descriptive method with a qualitative approach. Data collection techniques were carried out by interviews, observation, and documentation. The results of the study show that the capacity of the Medan City BPBD in the Keltana Program in the Aur Village is still not good. From the dimension of human resources (HR), the training has not been carried out routinely. In the dimension of organizational strengthening, the utilization of personnel has not been maximized because Village Volunteers do not have adequate facilities and equipment. In the dimension of institutional reform related to economic and political rules, there are still many poor people who live on the banks of the river who still throw garbage into the river and the Keltana program has not been able to change the habits of the Aur Kelurahan community.